Insights into dynamic covalent chemistry at surfaces. Issue 91 (25th September 2015) - Plas, Jan; Waghray, Deepali; Adisoejoso, Jinne; Ivasenko, Oleksandr; Dehaen, Wim; De Feyter, Steven
Abstract : The potential of surface confined self-assembly to influence the chemical equilibrium of Schiff base formation and bias the yield and distribution of reaction products is explored. Abstract : The potential of surface confined self-assembly to influence the chemical equilibrium of Schiff base formation and bias the yield and distribution of reaction products is explored.